Obligation of carrying out the canonical visitation in religious Institutes - SZEWCZUL, BOŻENA (Prawo Kanoniczne, 2014)
Canonical visitation, existing in religious life from its monastic early stage, are still very important for individual monks, religious communities and whole Institutes. They help to carry on a conversation between major Superiors and Subordinates, what is necessary for proper power exercising, as well as a development of a spiritual and fraternal life. Visitations - thanks to their completeness, including the whole of a given Institute’s life - may help in the improvement of observing the religious law, and become a good remedy against monks’ individualism and isolation from their community. Canonical visitation may still be useful, due to its flexibility, provided by the General Legislator, who leaves detailed regulation to Institute’s own law. Therefore the visitation’s value, effectiveness, modernization, and its conformity with needs of Superiors and visited Monks, finally depends only on nothing but the Institute’s members and their superiors.